India's Naya Theater Company at a lecture/demonstration by Habib Tanvir - Naya Theater Company; Tanvir, Habib; Tanveer, Moneeka Misra; Tanvir, Nageen:::Creator::::::::::::
Two page promotional flyer for an event including a lecture, demonstration, and video screening of a play by Habib Tanvir, titled Charandas Chor (Charan the Thief).